IDENTIFICATION OF AREAS AND HOUSING CONDITIONS IN TORNADO-PRONE AREAS IN SERDANG BEDAGAI REGENCY - Christop HS. Pangaribuan; Abdi Sugiarto; Cut Nuraini (Yayasan Sinergi Multidimensi Kreatif, 2025)
The tornado disaster is one of the natural disasters that often occur in Indonesia, including in Serdang Bedagai Regency. Therefore, research is needed that aims to analyze areas prone to tornado disasters and the level of house damage caused as a basis for reference for rehabilitation and reconstruction of disaster victims' houses in Serdang Bedagai Regency. The methodology used is qualitative methods and quantitative methods through field survey approaches, geographical mapping, and data sources belonging to the Regional Disaster Management Agency of Serdang Bedagai Regency and even interviews with local residents. The results of the identification in this study show that the occurrence of tornado natural disasters from 2021 to 2024 has occurred 43 times at 124 different points and affected 1,020 housing units, which are predominantly occurring in Sei Bamban and Tanjung Beringin Districts because they are lowland and open, namely rice fields and near-coastal areas. The results of this study are expected to be a reference for local governments in disaster mitigation planning.